Prematurity and Morbidity: Could KMC Reverse the Process? - Tessier, Rejean; Cristo, Martha; Nadeau, Line; Schneider, Cyril (Current Women's Health Reviews, 2011)
The slow progress, indeed the ineffectiveness, in checking the rise in preterm births is undoubtedly partly due to the inaccuracy of predictive models, our focus on curative interventions, and the dearth of prevention strategies in this public health sector. Moreover, results from meta-analyses of observational studies concluded that premature or low birth weight subjects have cognitive deficits, poorer academic performance, attention problems and are less socially competent than their full-term peers, and that these consequences have long lasting impacts on adolescence and adulthood. Can these effects be reversed? Could an intervention such as Kangaroo Mother Care reverse the short- and long-term negative effects of preterm birth? Recent interventions aimed at improving the intensive care unit environment have already shown positive effects on babies' physical growth, respiratory autonomy and length of hospitalization. The KMC program appears to act at a number of levels and in different time windows. In the very short term, it reduces length of hospitalization and exposure to the stressful intensive care unit environment. Since infants are carried by their parents, noise is reduced and absorbed by the latter's clothing and body. KMC allows parents to have early, close contact with their baby and at the same time strengthens the foundation for secure parentinfant bonding. Parents feel more positive and more confident regarding their preterm infant. They appear to accept the intervention and carry it out without any difficulty. The infants gain weight more rapidly, they breathe better, experience less apnea, maintain their body temperature better and have fewer iatrogenic problems due to long hospital stays. In the medium term (12 to 24 months), KMC appears to protect infants who are more fragile at birth. The latter obtain a higher developmental quotient (ranging from 10 to 13 points for the most fragile) than extremely preterm infants who receive traditional care and they benefit from a family environment (including father involvement) that is more dynamic and stimulating than fragile infants who did not receive KMC. However, a number of questions remain regarding the factors responsible for these changes. Given the current state of knowledge, the main hypotheses focus on the neurological changes that result from the intervention. This new neuroscientist approach we conduct in KMC proposes that different types of care can repair the brain to some extent at a critical age, that is, very early. The ancillary knowledge provided by neurophysiological studies on brain functioning should contribute to guide the medical and rehab interventions aimed at minimizing the long-term neurodevelopmental disability of children born preterm.
Keywords: High-Risk Preterm Infants